Weimar controversies : explorations in popular culture with Siegfried Kracauer - Fisher, Peter S., 1952- (Culture & theory, 2020)
In the Weimar Republic, popular culture was the scene of heated controversies that tested the limits of national cohesion. How could marginal figures like a stigmatized villager, a grub street writer, or an advocate for nudism become flashpoints of political conflicts? Peter S. Fisher draws on Siegfried Kracauer's trenchant observations on Weimar's contradictions to knit these exemplary stories together. Following his methodology, society's underdogs take center stage, pushing the headline makers into the background.